Tales of an educator, an administrator and a writer amidst Covid 19: an autoethnography / Rofiza Aboo Bakar - Aboo Bakar, Rofiza (Universiti Teknologi MARA, 2021)
This is a reflexive article that documents my experience of being an educator, while also embracing the role of a head of department and a writer, in a university in Malaysia during the first Movement Control Order (MCO) amidst the COVID 19 pandemic. Like other educators all around the world, I was thrown into the grey area of online learning which I had to prepare myself with. To take up all three responsibilities and be efficient at each one left me experiencing fear, emotional and mental exhaustion. However, supportive comments from some good friends, reading good books, and the analysis of videos I undertook for my little research stopped my lament. I then realised that I had to rise amidst the pandemic moment and be grateful for having these responsibilities as opposed to many others who had lost their jobs in the trying times. With regards to method, I documented my experiences from the day the MCO started through note making in a diary and WhatsApp messages sent to friends. I also kept the university correspondence materials in respect to the pandemic. The notes and materials helped in the process of writing this article. Through this autoethnographic exploration, the coping strategies taken to ease the struggle and the meaning of being grateful transpired. I hope that others who shoulder the roles of educators, administrators and writers are inspired to soon share their voices and add meanings to the complexity of these responsibilities, especially during the unusual times in human history.